Bilateral Medial Medullary Stroke: A Challenge in Early Diagnosis. (2nd October 2013) - Torabi, Amir M.
Abstract : Bilateral medial medullary stroke is a very rare type of stroke, with catastrophic consequences. Early diagnosis is crucial. Here, I present a young patient with acute vertigo, progressive generalized weakness, dysarthria, and respiratory failure, who initially was misdiagnosed with acute vestibular syndrome. Initial brain magnetic resonance imaging (MRI) that was done in the acute phase was read as normal. Other possibilities were excluded by lumbar puncture and MRI of cervical spine. MR of C-spine showed lesion at medial medulla; therefore a second MRI of brain was requested, showed characteristic "heart appearance" shape at diffusion weighted (DWI), and confirmed bilateral medial medullary stroke. Retrospectively, a vague-defined hyperintense linear DWI signal at midline was noted in the first brain MRI. Because of the symmetric and midline pattern of this abnormal signal and similarity to an artifact, some radiologists or neurologists may miss this type of stroke. Radiologists and neurologists must recognize clinical and MRI findings of this rare type of stroke, which early treatment could make a difference in patient outcome. The abnormal DWI signal in early stages of this type of stroke may not be a typical "heart appearance" shape, and other variants such as small dot or linear DWI signal at midline must be recognized as early signs of stroke. Also, MRI of cervical spine may be helpful if there is attention to brainstem as well.